Peroxisomal Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The biochemical and clinical diagnostic characteristics of peroxisomal disorders are reviewed by authors from the Department of Pediatrics, Medical University of South Carolina, Charleston, SC.